1958
DOI: 10.3109/00016355809064113
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Determination of Attrition and the Ensuing Tooth Migraton

Abstract: A s early :is 1879, Brocn proposed :I systeni for recording attri-(1 = no attrition 1 = attrition of the enamel only 2 = one or several islets of dentine visible, surrounded by enainel 3 = dentine visible on the whole occlusal surface i"1,'usure ;I produit uiie section coiiiplL:te de tout le fGt de 1:i dent.") 4 = the whole crown is \ w r n d o \ \ 7 1 1 :I$ far :is the neck. In his "I.echrbuc*h der AnthroyologiP" ,Il/rrfin (1928) used the Goldstein (1932 ) applied Hrdlickrr's clnssification, i.e. Slight we;ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…5,000 -2,500 years ago) (Nara et al, 1998). Although Lysell (1958a) reported that the tendency in medieval Swedish skulls was not statistically significant, a close examination reveals that his results do not provide clear evidence of the absence of mesial drift in the molars (P ϭ 0.05, one-tailed t-test, d.f. ϭ 28).…”
Section: Mesial Driftmentioning
confidence: 91%
See 1 more Smart Citation
“…5,000 -2,500 years ago) (Nara et al, 1998). Although Lysell (1958a) reported that the tendency in medieval Swedish skulls was not statistically significant, a close examination reveals that his results do not provide clear evidence of the absence of mesial drift in the molars (P ϭ 0.05, one-tailed t-test, d.f. ϭ 28).…”
Section: Mesial Driftmentioning
confidence: 91%
“…Although there is no corroborative evidence, most workers ascribe it to continuous lip tension counteracting continuous pressures from the tongue (Selmer-Olsen, 1937;Lysell, 1958a;Hylander, 1977;Frederick, 1991). Based on this concept, the following explanatory model can be formed: during development of the dentition, the protruding anterior teeth are in contact with their adjacent and/or opposing teeth in a form of scissors occlusion with no interproximal spaces (see "Anterior occlusion," below).…”
Section: Incisor Lingual Tippingmentioning
confidence: 99%
“…11,39,41 Past investigations identifi ed a large amount of tooth wear in primitive populations, where the prevalence of malocclusions was lower when compared with current groups. 10,[42][43][44][45][46][47][48][49][50][51][52] Previous studies have shown an increasing prevalence for certain malocclusions in the past 30 years of last century. 5,6 The aim of this study was to test whether there has been a signifi cant increase or decrease in the amount of wear of deciduous teeth during the same period, due to an occlusal aspect, possibly correlated to malocclusions.…”
Section: Discussionmentioning
confidence: 99%
“…1963], Investigation of the factors affecting crown size may also be complicated by the relationship with body size [Brace and Montagu, 1965;Lavelle Anderson and Thompson, 1973], although such a relationship has been denied by Bailit and F riedlaender [1966]. Attrition is another factor which complicates the investigation of crown size [Lundstrom, 1952], and attempts to correct for the loss of tooth substance due to attrition [Ashton and Zuckerman, 1950a;Robinson, 1956;Lysell, 1958] have yet to withstand critical analysis. Finally, the univariate statistical analysis of odontometric data is another feature which may inhibit the elucidation of the roles of genetic and en vironmental factors in crown size, since it enables only one or two tooth dimensions to be compared at any one time rather than the dentition as a whole [Potter, 1972].…”
Section: Introductionmentioning
confidence: 99%